A Few Good Masks : Evidence from Mask Manufacturing in Rwanda during the COVID-19 Pandemic - Byrne, Kieran; Kondylis, Florence; Loeser, John; Mukama, Denis (World Bank, Washington, DC, 2022)
Did increases in mask supply slow the spread of COVID-19 Rwanda licensed and incentivized textile manufacturers to produce high-quality masks at the start of the COVID-19 pandemic. This paper exploits spatial variation in exposure to mask manufacturing through textile trade networks within an event-study design using receipt-level tax data. Licensing domestic mask manufacturers conservatively reduced mask prices by 8.8% and reduced monthly growth in COVID-19 infections (proxied by demand for anti-fever medicine) by 12%. The dynamics of the results suggest that increased mask quality explains reduced infections, in a context where there was strict enforcement of mask mandates and informal markets for masks.